2017
DOI: 10.1590/0102-311x00035716
|View full text |Cite
|
Sign up to set email alerts
|

Características e fatores associados à hospitalização nos primeiros anos de vida: coorte de nascimentos de Pelotas de 2004, Rio Grande do Sul, Brasil

Abstract: Hospitalization is a frequent event in early childhood. In Brazil, the , and was highest in the first year (19.1%;, remaining stable at approximately 10% between the first and fourth years, decreasing to 8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
(59 reference statements)
2
5
0
3
Order By: Relevance
“…Our results on respiratory health in childhood are in line with studies showing an increased risk of hospitalisation and respiratory problems during childhood for children of low BW [ 40 , 41 , 42 , 43 ]. A recent follow-up study on 118,166 German children assessed how the cumulative costs for hospital treatment in the first 4 years of life of low BW infants are about EUR 1300 higher than for infants of normal BW [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our results on respiratory health in childhood are in line with studies showing an increased risk of hospitalisation and respiratory problems during childhood for children of low BW [ 40 , 41 , 42 , 43 ]. A recent follow-up study on 118,166 German children assessed how the cumulative costs for hospital treatment in the first 4 years of life of low BW infants are about EUR 1300 higher than for infants of normal BW [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…O resultado no ano de 2019 é semelhante ao encontrado na investigação que propôs analisar as características da hospitalização de crianças nos seis primeiros anos de vida. Os autores verificaram que as doenças do aparelho respiratório estiveram entre as principais causas de hospitalização em todos os anos, com um percentual de 9,6% no 1.º ano de vida, seguidas de 5,0% entre 1 e 4 anos e tendo declínio nos anos subsequentes 19 .…”
Section: Discussionunclassified
“…Respiratory diseases, in general, are one of the main factors associated with hospitalization in the first 6 years of life. ( 19 ) Thus, we believe that the significant correlation between functional decline, use of MV and sedatives found in our study may also be related to the profile of patients, since most admissions to this pediatric ICU occurred due to respiratory illnesses. Previous studies conducted in the same pediatric ICU also reported respiratory illnesses (40% and 43%) as the most frequent causes of admission.…”
Section: Discussionmentioning
confidence: 55%